Digital Business Model for CREATIVE INDUSTRIES - Palilingan, Verry Ronny; Batmetan, Johan Reimon (JR Education, 2022)
Digital business plays a significant role in industry 4.0. Many companies rely on information technology to connect customers, employees and run their management. Many digital startups are growing very fast in Indonesia but do not have a strong and good business model to maintain sustainability. This study aims to develop a way of analyzing a digital startup's business model so that it becomes a profitable startup. The method used in this study is a method of analyzing business models using a lean canvas. The results of this study show that lean canvas can produce a strong and sustainable business model for digital startup significantly. This study concluded that lean canvas is very good for building a business model on digital startup